Cone-beam computed tomography performance and endodontic filling material influence in the diagnosis of horizontal root fracture - Naeime Rayiat; Zahra Sadat Madani; Ehsan Moudi; Ali Bijani (Babol University of Medical Sciences, 2020)
Introduction: The aim of this study was to investigate the accuracy of Cone-beam computed tomography(CBCT) in detecting the horizontal root fractures (HRFs) in teeth with and without gutta-percha. Materials & Methods: This in vitro study was performed on 100 mandibular and maxillary single-rooted teeth. In 55 samples, the canals were prepared. Then, the horizontal fracture was induced randomly in 56 (29 with gutta-percha, 27 without gutta-percha) samples. The samples were mounted on a wax rim, and the CBCT scan was provided. The scans were examined by two endodontists twice with two-week interval. Data were analyzed using IBM SPSS 20.0 software (IBM Corp., Armonk, IL, USA). Sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), likelihood ratio (LR +, LR -) with 95% confidence interval were calculated. Results: The sensitivity and specificity were 72% and 100% for the group with gutta-percha as well as 89% and 100% for the group without gutta-percha, respectively. The coefficient of agreement for each observer within two observations was 0.940±0.034 and 0.960±0.028 (P<0.001). The inter observer agreement was 0.092±0.039 (P<0.001). Conclusion: The CBCT scans have high accuracy in diagnosis of horizontal root fracture and gutta-percha although they reduce the diagnostic accuracy with no significant effect.